Routing optimization method of WSN based on improved ant colony algorithm - Han ZHAO; Shaoqing HUANG (Dianxin kexue)
Wireless sensor network is a self-organizing network that storing and transferring the data by the interconnected nodes.It will promote the development of the internet of things technology.In order to optimize the ability of data communication and data process，and reduce the energy consumption，the routing optimization method of wireless sensor network based on improved ant colony algorithm was proposed.Improved ant colony algorithm had excellent global optimization ability，so it could be used to optimize the minimum hop routing problem in wireless sensor network.And the simulation proves its validity.